Rapid, Accurate and Sensitive Determination of Fenpropathrin as Insecticide in Dried Strawberry Samples by High Performance Liquid Chromatography, and In Vivo Stability and Behavior under Gastric Conditions - Tekin, Zeynep; Zaman, Buse Tugba; Bakirdere, Sezgin (OXFORD UNIV PRESS, 2020)
An analytical method was validated for the determination of fenpropathrin in dried strawberry samples using RP-HPLC. Under the optimal conditions, LOD was obtained as 3.2 mu g L-1. The method demonstrated good linearity (R-2 > 0.9997) and satisfactory repeatability (%RSD <= 4.12) at low concentrations. The validated assay was applied to spiked samples. High percent recovery values were obtained. The analyte was subjected to simulated gastric conditions, and no major change of the analyte peak areas and retention time throughout 300 min was observed.
Keywords: Fenpropathrin; Gastric conditions; High performance liquid chromatography; PYRETHROID INSECTICIDES; RESIDUES; FRUIT; MICROEXTRACTION; EXTRACTION; Chemistry